CE: Human Papillomavirus–Related Oropharyngeal Cancer. (August 2016) - McKiernan, Janet; Thom, Bridgette
Abstract : N/A: The overall incidence of head and neck cancer—which includes laryngeal, hypopharyngeal, nasal cavity, paranasal sinus, nasopharyngeal, oral, oropharyngeal, and salivary gland cancers—has declined in the United States over the past 30 years with the concomitant reduction in tobacco use. Over that same period, however, the worldwide incidence of oropharyngeal cancer has escalated significantly, most notably among men and women under age 60 who live in developed countries. This epidemic rise in oropharyngeal cancer is largely attributed to certain genotypes of the human papillomavirus (HPV). In the United States, HPV prevalence in oropharyngeal tumors increased dramatically, from roughly 16% between 1984 and 1989 to nearly 73% between 2000 and 2004, and the annual incidence of HPV-positive oropharyngeal cancer is expected to surpass that of HPV-related cervical cancer by 2020. This article provides an overview of head and neck cancer—its incidence, risk factors, treatment, and posttreatment sequelae—with a focus on HPV-related oropharyngeal cancer. Unlike other forms of head and neck cancer, HPV-related oropharyngeal cancer tends to affect younger patients with few or none of the traditional risk factors and has a distinctive presentation, histology, and natural course. In order to provide appropriate patient education and to help these patients monitor and manage late and long-term treatment effects, it is important for nurses to be aware of this disease and its treatment, and of the unique survivorship issues that arise for affected patients. Abstract : This fourth article in a series on cancer survivorship care from the Memorial Sloan Kettering Cancer Center provides an overview of the incidence, treatment, and posttreatment sequelae of head and neck cancer, with a focus on HPV-related oropharyngeal cancer and the unique survivorship issues it creates.